THERMAL PROCESSES IN VENTILATED DISC BRAKES AND THEIR SIMULATION IN TYPE II TESTS - Захара, Ігор; Козак, Федір (SWorldJournal, 2023)
Modern motor vehicles (motor vehicles) are characterized by the fact that their operational properties are constantly improved, which ensure an increase in their productivity and capacity of highways due to an increase in the average speed of traffic. As